Food safety knowledge, attitudes, practices and trust of pork consumers of Northern Vietnam - Unger, Fred; Nga Nguyen Thi Duong; Huyen Le Thi; Phuc Pham Duc; Sinh Dang-Xuan; Grace, Delia (International Livestock Research Institute, 2022)
Objectives: Consumer demand for safe food has been defining the development of value chains. Demand is influenced by consumer knowledge, attitudes, and practices (KAP), governance and trust in the value chain among other factors. The study aimed to evaluate consumers KAP about food safety in selected pork value chains in Vietnam. Here we present KAP results being part of larger project on food safety interventions in pork retail in Northern Vietnam. Materials and Methods: A food safety performance tool containing of three main pillars: safety, scalability and societal concerns was used to assess food safety KAP, trust and governance of 188 consumers randomly selected from different pork value chains (modern and traditional) in Hanoi, Hung Yen, Hoa Binh and Nghe An provinces using key informant interviews. Results: Pork value chains are transitioning, with greater attention to consumer demands for safer products, yet some consumer misconceptions about food safety were observed with only little concern given to microbial contamination, the confirmed most important hazard from recent representative surveys. Proper attitudes on foodborne illness and applying good hygiene practices in households were obtained from interviewed participants. Whereas consumers overall have low trust in value chain actors, including those important for food safety (i.e., farmers and input suppliers), and highly ranked food safety responsibility of pig producers and government authorities. Trust was found higher in rural versus urban areas. Among communication channels, higher trust was placed in television news from the government while lower trust to social media. Conclusions: To be competitive, pork value chains should focus on product differentiation, such as signalling good practices and organizing a shorter chain, including cooperatives model, with focus on product traceability. Government could support this process by implementing targeted communication about food safety to consumers and all chain actors.